Strategi Marketing Communication sebagai Upaya Mempertahankan Eksistensi Lido Lake Resort by MNC Hotel Pasca Akuisisi - Saputra, Andien Putri Aliffia; Suparman, Suparman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the marketing communication strategy implemented by Lido Lake Resort by MNC Hotel in maintaining brand existence after its acquisition by MNC Land. A qualitative descriptive approach was applied, utilizing observation, in-depth interviews, and documentation. Informants including marketing managers, and communication staff were selected through purposive sampling. Data were analyzed using thematic analysis involving coding, categorization, and theme development, validated through source triangulation and member checking. The results reveal three main findings: (1) 85–90% of the marketing budget was allocated to digital channels emphasizing social media optimization, (2) influencer collaboration became the core strategy to expand market reach and engagement, and (3) synergy within the MNC ecosystem and the Special Economic Zone (KEK) Lido City strengthened hotel visibility and brand perception. Effectiveness was reflected through digital interaction growth, audience reach expansion, and improved brand image among guests. The findings highlight the importance of consistent cross-channel messaging and brand identity reinforcement during post-acquisition integration.